Matemática no percurso formativo de futuros professores dos anos iniciais a - martins, ana patrícia (2021)
Considering the importance of History of Mathematics (HM) in the Mathematics teaching and the need for its approach in the initial training of teachers, this study aims to: characterize the use of HM in the educational trajectory of future teachers (FT) in basic and secondary levels; describe their training in HM in the Basic Education (BE) degree; and identify these FT's conceptions about the importance of using HM in Mathematics teaching. In this study, 63 female FTs participated in this study, graduated in BE in Portuguese institutions and starting a professional master's degree. Data collection resulted from the application of a questionnaire, with two parts: Teaching/Training with/in HM; and Conceptions about the contributions of HM to Mathematics teaching. The results reveal that 68% of the FT consider non-existent, or limited to episodic moments, the use of HM in their Mathematics classes during their primary and secondary education; FT also consider that training in HM during the BE course was frequent (52%) or solid (17%). The use of HM is evaluated positively because facilitates the understanding of the contents, illustrate the usefulness, importance and connections of Mathematics, and allows different approaches and developing transversal skills.